PENGEMBANGAN VIDEO PEMBELAJARAN ANEMIA PADA REMAJA BERBASIS MOTION GRAPHYC - Puriningsih, Konita Rhamadani; Astuti , Aprilina Dwi; Marwiyati , Marwiyati; Hakim, Herry Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Motion graphic is a media that includes audio visual media so that its use can facilitate student understanding, strengthen memory, and attract students' attention and interest. The use of motion graphics in the process of developing learning videos is intended to increase interest in learning and increase students' digestibility of the information on the subject matter provided. The purpose of this study is to develop a learning video based on Motion graphic Anemia in Adolescents. This study uses a qualitative descriptive method, the research process goes through three stages, namely pre-production, production and post-production. The techniques applied include puppet pin tool, 2D animation and visual effects on illustration objects. The results of this study The Puppet pin tool technique can animate character movements and produce flexibility in objects that make the objects more realistic. The 2D animation technique is applied by applying the principles of 2D animation including squash and stretch, anticipation, follow through and overlapping as well as timing and spacing to create more lively and interesting animations so that the movements produced by the animation look more natural. The visual effects applied include drop shadow, gaussian blur, and optical flare, which have succeeded in improving visual quality and greater appeal to the work. ABSTRAK Motion graphic merupakan media yang mencakup media audio visual sehingga penggunaannya dapat mempermudah pemahaman siswa, memperkuat ingatan, serta menarik perhatian dan minat siswa. Pemakaian motion graphic dalam proses pengembangan video pembelajaran dimaksudkan untuk meningkatkan minat belajar serta mempertinggi daya cerna siswa terhadap informasi materi pelajaran yang diberikan. Tujuan dari Penelitian ini untuk mengembangkan video pembelajaran berbasis Motion graphic Anemia Pada Remaja. Penelitian ini menggunakan metode diskriptif kualitatif, proses penelitian melalui tiga tahapan yaitu pra produksi, produksi dan pasca produksi. Teknik yang diterapkan meliputi puppet pin tool, 2D animation dan visual effect pada objek ilustrasi. Hasil dari penelitian ini Teknik Puppet pin tool dapat menganimasikan pergerakan karakter dan menghasilkan kelenturan pada objek yang menjadikan objek tersebut lebih realistis. Teknik 2D animation diterapkan dengan mengaplikasikan prinsip-prinsip 2D animation meliputi squash and stretch, anticipation, follow through and overlapping juga timing and spacing untuk menciptakan animasi yang lebih hidup dan menarik sehingga gerakan yang dihasilkan oleh animasi terlihat lebih alami. Visual effect yang diterapkan meliputi drop shadow, gaussian blur, dan optical flare berhasil meningkatkan kualitas visual dan daya tarik lebih terhadap karya